Reading the Tea Leaves of Tumor-Mediated Immunosuppression - Orentas, Rimas J. (2013)
Polyphenol E, available as Polyphenon E, is a green tea extract whose activity can be benchmarked to the presence of specific catechins such as EGCG (epigallocatechin 3-gallate). Herein, Polyphenon E is shown to reverse myeloid-derived suppressor cell (MDSC) activity, linking the activity of a natural product extract to cell-mediated immunity.